Improved model for investigating transient stability in multimachine power systems - Ali Hamzeh; Zakaria Al-Omari (Institute of Advanced Engineering and Science, 2019)
The determinant factor in transient stability study of electric power systems is the behavior of synchronous generators when subjected to sudden and large disturbances. The objective of this paper is to develop a mathematical model, general algorithm, and a computer program to investigate the transient stability of multi-machine power systems. The developed mathematical model is established as a first step. The new developments lie in modeling the fault occurrence and fault clearance as well as the procedure of computing the system matrices during and after the fault through only modification of the matrix before the fault. Based on the developed mathematical model, a general algorithm was built and translated into a computer program using an object-oriented and visual language called Delphi. The algorithm adopted the Runge-Kutta method for numerical solution of differential swing equations and was programmed within the program. The developed program was validated by applying it to small sample electrical networks. The program was used to analyze the transient stability of a relatively large test network and accurate results were obtained that could be relied upon for protective relays settings and optimization of control system parameters. It was found that the developed program is an effective and rapid tool for estimating transitory stability for real power systems.